2011
DOI: 10.1016/j.biopsycho.2010.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Social support and the reactivity hypothesis: Conceptual issues in examining the efficacy of received support during acute psychological stress

Abstract: Social support has been reliably related to better physical health outcomes. One influential model suggests that social support is related to lower cardiovascular disease mortality because it reduces the potentially deleterious consequences of cardiovascular reactivity during acute stress. However, received support and perceived support are separable constructs and epidemiological research suggests variability in links between received support and health. This is important because most social support and acute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
102
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(107 citation statements)
references
References 56 publications
3
102
0
2
Order By: Relevance
“…Importantly, to the authors' knowledge, only a few studies have examined the conjoined impact of both types of social support on cardiovascular responses during an acute laboratory challenge. The study of conjoined effects seems particularly important because a history of previous positive experiences of social support could have an impact on the effect of enacted social support in a particular situation [20,24]. For example, it has been suggested that past experiences with naturalistic support could signify implicit support and reduce threat appraisals in light of aversive encounters when a third party is present during a laboratory challenge [37].…”
Section: Aim Of the Studymentioning
confidence: 99%
See 2 more Smart Citations
“…Importantly, to the authors' knowledge, only a few studies have examined the conjoined impact of both types of social support on cardiovascular responses during an acute laboratory challenge. The study of conjoined effects seems particularly important because a history of previous positive experiences of social support could have an impact on the effect of enacted social support in a particular situation [20,24]. For example, it has been suggested that past experiences with naturalistic support could signify implicit support and reduce threat appraisals in light of aversive encounters when a third party is present during a laboratory challenge [37].…”
Section: Aim Of the Studymentioning
confidence: 99%
“…For example, stressful situations in daily life often imply that individuals are faced with an aversive encounter while they are alone (because social support is not available in a particular situation), but receive social support before or after the occurrence of a stressor. Moreover, it should be noted that this paradigm is dissonant with operationalizations of social support as applied in epidemiological research linking support to disease [19,20]. Thus, it would be necessary to relate such naturalistic measures of social support to cardiovascular reactivity in the laboratory.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Supportive interpersonal relationships include service provider and recipient, as can be the case for the AF programs, such as AFW2. In some cases, as described briefly above, support from providers can be more effective than support from close relationships (e.g., Sarason and Sarason, 2006;Taylor, 2011;Uchino et al, 2011), although natural support networks can also be incorporated into treatment.…”
Section: Social Functioningmentioning
confidence: 99%
“…Often, published interventions focus on support that strangers, such as in peer support groups, provide (Cohen, 2004). In some cases, such as when relationship quality is poor or the supporters' own distress impedes support provision, these can actually be more effective than support that close relationships (i.e., marital) provide (see, e.g., Sarason and Sarason, 2006;Taylor, 2011;and Uchino et al, 2011).…”
Section: Social Functioningmentioning
confidence: 99%